2011
DOI: 10.1007/s10979-009-9198-4
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of interrogative suggestibility in Miranda rights comprehension in adolescents.

Abstract: This study aimed to further clarify the association between interrogative suggestibility and Miranda rights comprehension in adolescents; in particular, we examined whether intellectual ability (IQ) serves as a mediator of this relationship. Participants completed Grisso's Miranda Instruments, the Wechsler Abbreviated Scale of Intelligence, and the Gudjonsson Suggestibility Scale. Many youth demonstrated poor comprehension of their rights, particularly younger and less intellectually capable adolescents. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 45 publications
12
26
0
Order By: Relevance
“…These findings are also consistent with previous tests of how well youths and adults comprehend the legal rights contained in police cautions and warnings (e.g., Davis, Fitzsimmons, & Moore, 2011;Eastwood & Snook, 2009;Grisso, 1981;McLachlan et al, 2011). Our exploratory test of youth comprehension of a youth waiver form, which had a medium level of complexity relative to other waiver forms, showed that the participants understood less than half of the rights contained in that waiver form.…”
Section: Results the Average Percentage Comprehension For The Final supporting
confidence: 90%
See 1 more Smart Citation
“…These findings are also consistent with previous tests of how well youths and adults comprehend the legal rights contained in police cautions and warnings (e.g., Davis, Fitzsimmons, & Moore, 2011;Eastwood & Snook, 2009;Grisso, 1981;McLachlan et al, 2011). Our exploratory test of youth comprehension of a youth waiver form, which had a medium level of complexity relative to other waiver forms, showed that the participants understood less than half of the rights contained in that waiver form.…”
Section: Results the Average Percentage Comprehension For The Final supporting
confidence: 90%
“…In one of the first studies of youth caution comprehension conducted in the United States, Grisso (1981) found that only 21% of juveniles fully understood the Miranda warning that was presented to them. Subsequent studies of Miranda comprehension in juveniles have found similarly low levels of understanding legal rights and the consequences of waiving those rights (e.g., Goldstein, Condie, Kalbeitzer, Osman, & Geier, 2003;McLachlan, Roesch, & Douglas, 2011;Viljoen, Zapf, & Roesch, 2007).…”
mentioning
confidence: 98%
“…Specifically, students in the higher grades tended to outperform students in lower grades in their overall recall of information in the waiver forms and their ability to recall the five main rights. This trend is consistent with previous findings that age is a predictor of Miranda comprehension in juveniles (Goldstein et al, 2003;McLachlan et al, 2011). Although we did not directly measure the intellectual ability of students, we suspect that this trend is due to cognitive differences (e.g., working memory and attention) between younger and older students (Luna, Garver, Urban, Lazar, & Sweeney, 2004;Yurgelun-Todd, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Subsequent research in Scotland, the USA, and Canada confirmed that youths failed to comprehend their legal rights and-in line with what is known about brain maturation processes (Yurgelun-Todd, 2007)-that younger youths tend to exhibit the lowest levels of understanding (e.g., Abramovitch, Peterson-Badali, & Rohan, 1995;Cooke & Philip, 1998;Goldstein et al, 2003;McLachlan, Roesch, & Douglas, 2011;Viljoen, Zapf, & Roesch, 2007). In an initial preliminary test of the comprehensibility of Canadian youth waiver forms-which contained the enhanced protections provided by the YCJA- Eastwood et al (2012; Study 2) presented a single waiver form to a sample of high school students.…”
mentioning
confidence: 68%
“…In their analysis of 152 juvenile defendants, Viljoen, Zapf, and Roesch (2007) found a clear link between age and impaired Miranda comprehension: 11-13 years (58.0% impaired), 14-15 years (33.3% impaired), and 16-17 years (7.8% impaired). This relation of age to impaired Miranda comprehension has been clearly established in both offender (Colwell et al, 2005;Riggs-Romaine, 2008) and community (McLachlan, Roesch, & Douglas, 2010;Woolard, Cleary, Harvell, & Chen, 2008) samples. Closely aligned with age, maturity also plays an important role in Miranda comprehension (Cauffman & Steinberg, 2000).…”
Section: Miranda Comprehension and Reasoningmentioning
confidence: 82%